ESG Implementation through Management Control Systems in Developed and Developing Countries: A Literature Review and Bibliometric Analysis - Dahlia Tri Anggraini; Tubagus Ismail; Elvin Bastian; Nurhayati Soleha (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to identify and synthesize research developments on the role of Management Control Systems (MCS) in supporting Environmental, Social, and Governance (ESG) implementation and to identify future research opportunities. Method: A literature study using a Systematic Literature Review (SLR) approach to articles examining the relationship between MCS and ESG across various organizational contexts. Data were analyzed qualitatively by identifying, selecting, and classifying themes and synthesizing relevant research findings. Results: the study indicates that most studies still focus on MCS aspects of internal control, internal control quality, internal control personnel experience, and internal control costs in supporting ESG performance. In addition, the dominant theories used are legitimacy theory, institutional theory, stakeholder theory, and signaling theory. The findings also indicate that a good quality internal control system contributes to improved ESG performance and stakeholder trust. The implications of this study underscore the importance of strengthening MCS as a strategic instrument for supporting ESG-based sustainable business transformation. Novelty: The novelty of this research lies in the comprehensive synthesis of the relationship between MCS and ESG and the identification of research gaps, which show that previous studies are still dominated by the internal control perspective, thus opening up opportunities for the development of a broader MCS model with a qualitative, multidimensional approach, and focusing on ESG implementation in developing countries.